Carbohydrate antigen 125: an emerging prognostic risk factor in acute heart failure?. Issue 6 (12th December 2006) - Núñez, Julio; Núñez, Eduardo; Consuegra, Luciano; Sanchis, Juan; Bodí, Vicent; Martínez-Brotons, Angel; Bertomeu-González, Vicente; Robles, Rocio; Bosch, Maria J; Fácila, Lorenzo; Darmofal, Helene; Llàcer, Angel
Abstract : Objective: To assess whether circulating levels of carbohydrate antigen 125 (CA125) predict subsequent 6-month all-cause mortality in patients after the index hospitalisation for acute heart failure (HF). Design and setting: Prospective cohort study at a single teaching centre in Spain. Methods: 529 consecutive patients with acute HF admitted in a single university centre were analysed. In addition to the traditional clinical information, CA125 (U/ml) was measured during the early course of hospitalisation. The independent association between baseline CA125 and mortality was assessed with Cox regression analysis. The follow-up was limited to 6 months. Results: 349 (66%) patients showed serum levels of CA125 >35 U/ml (established cut-off point value). At a 6-month follow-up, 89 (16.8%) deaths were identified. A positive trend between mortality and CA125 quartiles was observed; 3.8%, 15.2%, 22% and 26.5% of deaths occurred from quartile 1 to 4 of CA125 (p<0.001). Likewise, a monotonic, ascending trend in the risk ratios was estimated from the multivariable Cox model. Compared with the first quartile of CA125, the HRs (95% CI) for the second, third and fourth quartiles were 3.25 (1.20 to 8.79), 4.91 (1.88 to 12.85) and 8.41 (3.24 to 21.79), respectively. Conclusions: Serum levels of CA125 obtained in patients admitted with a diagnosis of acute HF was shown to be an independent predictor of mortality up to the 6-month follow-up.